Analysis of Genetic Potential of Banyuwangi Local Rice (Oryza sativa L.) Based on Relative Expression of Homogentisate Geranylgeranyl Transferase (HGGT) and Granule-Bound Starch Synthase I (GBSSI) Gene - Dyati Galuh Pratita; Tita Putri Milasari; Elhah Nailul Khasna; Sunarmi Sunarmi; Evi Susanti; Suharti Suharti; Delia Wahyu Pangesti; Annasa Sabatia; Dwi Listyorini (HAYATI Journal of Biosciences, 2021)
Rice nutrition including vitamin and amylose contents become important aspect for many people around the world. Rice with high amylose content (low glycemic index) is good for those with Diabetes mellitus. Tocotrienol, one precursor of Vitamin-E biosynthesis is catalyzed by enzymes encoded HGGT, while amylose biosynthesis is catalyzed by enzymes encoded GBSSI. The objective of this study was to find rice varieties with high tocotrienol and/or amylose content based on the expression of HGGT and GBSSI among eight Banyuwangi local rice varieties. Relative expression of HGGT and GBSSI was measured by qRT-PCR and analyzed using 2ΔCt method. Statistical analysis resulted in the significantly different of HGGT and GBSSI relative expression among samples. Relative expression of HGGT from the highest to the lowest were demonstrated by Hitam Melik, Hitam Pekat, Blambangan A3, Merah Bali, Blambangan A2, Berlian, Janur Kuning, and SOJ A3, respectively; while relative expression of GBSSI from the highest to the lowest were demonstrated by Hitam Melik, Hitam Pekat, SOJ A3, Janur Kuning, Berlian, Merah Bali, Blambangan A3, and Blambangan A2, respectively. Based on this research we conclude that Hitam Melik potentially produces higher tocotrienol and lower glycemic index than other studied varieties.